Changes of CA19-9 levels and related influencing factors in patients with type 2 diabetes mellitus after antidiabetic therapy - Xiafei Zhao; Yan Wang; Ling Zhou; Aili Ye; Quanfeng Zhu (Scientific Reports)
Abstract Abnormalities of carbohydrate antigen 19 − 9 (CA19-9) are common in patients with type 2 diabetes mellitus (T2DM), and in some patients, CA19-9 returns to normal level after glycemic control. The aim of this study was to investigate the factors associated with CA19-9 levels in patients with T2DM and the associated influences on the degree of reduction of CA19-9 levels after antidiabetic therapy (AT). This study was an observational cross-sectional study. A total of 213 patients with T2DM were enrolled in this study, of whom 105 with abnormal CA19-9 and 108 with normal CA19-9. Socio-demographic information, complete blood counts, biochemical indicators, thyroid function indicators, and CA19-9 level were collected separately for each subject. Levels of glycosylated hemoglobin, type A1C (HbA1c), fasting blood glucose (FBG) were significantly higher in T2DM patients with abnormal CA19-9 compared to patients with normal CA19-9 (both FDR < 0.001). CA19-9 level was significantly and positively correlated with neutrophil/lymphocyte ratio (NLR) (r = 0.16, P = 0.02), monocyte/lymphocyte ratio (MLR) (r = 0.16, P = 0.02), and FBG (r = 0.38, P < 0.001), while significantly and negatively correlated with free triiodothyronine (FT3) (r=-0.22, P = 0.002) and albumin count (r=-0.18, P = 0.007). After AT, the degree of decrease in CA19-9 level in T2DM patients with abnormal CA19-9 was significantly positively correlated with degree of decrease in FBG (r = 0.33, P < 0.001), as well as CA19-9 level before AT (r = 0.73, P < 0.001), NLR (r = 0.20, P = 0.04), and MLR (r = 0.25, P = 0.01). In this study, we investigated the influencing factors associated with CA19-9 level and the factors influencing degree of CA19-9 reduction after AT in T2DM patients with abnormal CA19-9.